PERAN LITERASI KEUANGAN DAN PERKEMBANGAN TEKNOLOGI FINANSIAL TERHADAP MINAT BERINVESTASI PADA MASA PANDEMI COVID19 - Novia Utami; Marsiana Luciana Sitanggang (Jurnal Serina Ekonomi dan Bisnis, 2023)
This study aims to analyze the relationship between the use of financial technology and financial literacy onthe interest of millennial and generation Z investors in investing in the capital market. The analysis wascarried out on 150 respondents with the sample selection method using convenience sampling, namely theages of 10 to 30 years or millennials and generation Z in Indonesia. The hypothesis testing technique usesthe multiple linear regression Ordinary Least Square (OLS) method. This research concludes that financialtechnology (fintech) does not influence investment intentions, while financial literacy influences investmentintentions.